Trabalhadoras do sexo e a conformação mercantil da sociedade - Amparo, Gabriela Albino do [UNIFESP] (2020)
This study aims to contribute to the discussion about the structuring conditions of female prostitution within the capitalist mode of production, dealing with the specificities of the work of women in situations of prostitution who work in the port region of the Santos’s city. Through the historical resumption of the conditions that made the emergence of the activity possible, intrinsically linked to the reconfiguration of the colonial city to the urban city, we seek to understand the totality of its development, apogee and, later, the decay of the bohemian zone, accompanying the remarkable intensification exploitation process and precarious working conditions. Thus, in order to follow the path that reconstitutes the process of forming sex work, the category of work is used, to understand the formation of the social being, and freedom, in order to discuss the possibilities of choice. The clarity of the oppression category - binomial formed by domination and exploitation - of female bodies is also central to the study of the theme. It then starts to understand how the cooptation exercised by the capitalist system weakened vital activity (work), transforming it into an imposed and compulsory activity. This apprehension is accompanied by the approach of the insertion of female labor in the world of capital, the deepening of hierarchical relations of power, of patriarchy, aligned with the conditions of production and reproduction of women in the context of the current system, and how the dynamics of these mechanisms was decisive for the reconfiguration of the socio-sexual division of labor. In this way, it is under the framework of capitalism that the sexual exploitation and oppression of bodies, substantially the female ones, intensify. Sex work takes on different shapes, permeated by the socio-sexual division of labor and the transformations in the world of work. Then, in the light of this theoretical basis, the experiences of sex workers who work in the port area of Santos will be analyzed.